Bourgain-Brezis’s duality argument for continuous primitives - Annalisa Baldi; Bruno Franchi (Bruno Pini Mathematical Analysis Seminar)
In this note we collect some results in ℝn about global Poincaré inequalities for differential forms obtained in a joint research with Pierre Pansu and presented by the authors in two seminars held in Bologna respectively in 2023 and 2024. At the end of the note we comment some very new results obtained in the Heisenberg groups ℍn.